GAMBARAN PENGETAHUAN KADER POSYANDU TENTANG PEMANTAUAN PERTUMBUHAN BALITA DI KECAMATAN TABANAN, KABUPATEN TABANAN - Sutrini, Ni Made Novi Ayu; Sutiari, Ni Ketut (ARCHIVE OF COMMUNITY HEALTH; Vol 12 No 1 (2025): April 2025, 2025)
ABSTRACT Monitoring the growth of toddlers is an important thing to do in an effort to find out and early detection if there are nutritional problems. Cadres as implementers of posyandu activities are expected to have knowledge about monitoring toddler growth. The purpose of this study was to determine the knowledge of toddler posyandu cadres about monitoring toddler growth in Tabanan District, Tabanan Regency. This study is a descriptive study using a cross sectional approach. The sample of this study was posyandu cadres in Tabanan District totaling 92 people, selected by systematic random sampling. The variables studied were age, education, occupation, length of time as a cadre, training or refreshing and the level of knowledge of cadres about monitoring toddler growth. Data were analyzed using univariate analysis. Most of the cadres (80.4%) had good knowledge about growth monitoring of children under five and there were cadres who had poor knowledge in the aspects of implementation (47.8%) and preparation (21.7%). Based on characteristics, a good level of knowledge is seen in cadres aged 41-50 years, cadres with the last education of Senior High School, cadres work as private employees and housewives, have become cadres for ? 9 years and cadres have attended training. Health agencies, namely the Health Office and Puskesmas, are expected to provide training or refreshing, especially on monitoring toddler growth in the aspects of preparation and implementation, which are held regularly and can use hands-on methods in addition to lecture methods. Keywords: Knowledge, Posyandu Cadres, Growth Monitoring, Toddlers